Still Undefeated: Exploring the Dimensions of Team Identity among Fans of a New College Football Team - Bob Heere Heere; Matthew Katz (Journal of Applied Sports Management, 2014)
The authors explore issues of team and university identification in the context of an upstart National Collegiate Athletic Association (NCAA) football program. University stakeholders, including students, faculty/staff, and alumni (N=3,191), of a large southwest university completed a multidimensional group identity scale to examine how these various stakeholder groups identify with both the university and the newly established team. Results indicate that these stakeholders largely disagreed with many of the identity constructs, indicating that the various processes of identity formation occur at different points in time. Furthermore, differences among the three stakeholder groups were identifies in regards to their identification with both the team and the larger university. Finally, the relationship between team identity and university identity was explored in order to empirically determine whether identifying with a college sports team impacts how individuals identify with the larger university. Managerial implications for a university implementing a new football program are detailed.
Keywords: team identity; college sports; community development